ANALISIS YURIDIS MENGENAI PENDAFTARAN TANAH DALAM PERSPEKTIF KONSEP WELFARE STATE - SYAHRIZAL EFENDI LUBIS (LP2MTBM MAKARIOZ, 2020)
Land has a major role in the dynamics of development, so in the Constitution 1945 article 33 paragraph (3) mentioned that theEarth, water and natural wealth contained therein are controlled by the state and used to sebesar-besar the prosperity of thepeople. The provisions on the land can also be seen in Law No. 5 of year 1960 concerning basic agrarian regulations or we arecommonly called with UUP A regulatory activities by the state that governs all life of society is an sovereignty that belongs to thestate. Government power is a form of power to do government to the people in order to create a condition that is conducive,safe and prosperous. Government based on the law, is a form of the consequences of the implementation of the rule of law. Insummary, the Government's government form includes every field, such as, law, politics, economics, social, culture, land andsecurity, as well as other areas relating to both the direct and indirect field of public life. Agrarian Field/land is a field that is alsoregulated by the government. Policy in agrarian field in Indonesia become a authority from Indonesian government. It is clearlydistributed in the CONSTITUTION 1945 and is spelled out through other implementing legislation. The Constitution of the year1945 mandated that land should be used for the sebesar-besar of people's prosperity. Land is not only a place of residence andfarming, but also has a value of bistoris, religious, political and security. Soil is also a factor in supporting economic growth,preserving the integrity and adhesives of the unitary Republic of Indonesia. Growing population growth and growingdevelopment will have an impact on land use change. Land use change will be shifting the use of land from farmland tonon-agricultural soil which will affect food production. The land that originally functioned as a cultivation (farming), graduallytransformed into multiutilization. The change from land use to agricultural utilization for non-farms has increased.